Políticas inclusivas no chão da escola : usinagens e rebeldias no front-da-batalha - Andrade, Ricardo Bodart de (2009)
The objective of this paper is to give visibility to the continuous process of inclusion, inevitable to every schooling process. We consider Education as a crucial battle field in the social net. Based on differential inclusion (HARDT e NEGRI, 2005) and using it as an instrument of analysis, we indicate in this research the insufficiency of the term exclusion for the comprehension of the contemporary (re)allocation processes (of people, communities, themes, etc.) through the capital. Either being in wealthier centers or in acute conditions of scarcity and ‘precariousation’, there’re only inclusions. Noticing the Public School as a conflictual weaving of this net, we discuss it as a production/producent of power/knowledge (FOUCAULT, 2006) and actions of social inclusion. Educators, students, families and communities invent themselves and life in a “school ground” inclusion policy. In attention to this ‘factoring’ managed in the daily encounters, we try to give visibility to the singular modes of using/doing the school/education. In this inevitable process of inclusion, we question the public condition of the Public School and the autonomy processes that crosses it. With this, we call less attention to the exclusion/inclusion that “The” school promotes, and more to how these movements compound within a moral-social restrain; to the production of tutelages and autonomies, life and labor conditions, solidarities, relationships among power, encounters that both caresses and hurts. Therefore, what matters, is not to take an inclusion policy as ‘something in itself’, to be applied in an accurate way, as a specialist thing, as an inevitable truth or inexorable action. That’s because such policy is digested in educators’, families’ and students’ anthropophagic elasticity, in an inventive ‘factoring’ of undergrowth and rebel inclusions in the daily battle front.